'Cast a Cold Eye': Life and Death in W. B. Yeats's Poetry. (4th May 2019) - Chang, Hawk
ABSTRACT: Acclaimed as one of the best poets of the twentieth century, William Butler Yeats is often the focus of critical attention. The connections between Yeats's work and the Abbey Theatre, Irish nationalism, language arts, and his love affair with Maud Gonne have been widely explored. Many of Yeats's poems focus on death, a universal topic which engenders fear and enchantment simultaneously, so his attitude toward the inevitability of decrepitude merits further exploration. This paper discusses Yeats's early poems, such as 'When You Are Old' and 'The Folly of Being Comforted' as well as his later poems, such as 'The Municipal Gallery Revisited' and 'A Dialogue of Self and Soul.' These poems are analysed in a comparative study of Yeats's conception of life and death. Additionally, Derrida's deconstructive reading strategy and his creative interpretation of death expounded in The Gift of Death (1996) are included to trace the elusive nature of death in Yeats's poetry and illustrate its personal and cultural implications. It was found that whereas in his earlier poems the hierarchical opposition of life and death is strategically subverted to help resolve his unrequited love affair, Yeats deals with death with energy and confidence in his later poems.